Dysplasia epiphysealis hemimelica: A huge articular mass with unpredictable surgical results - Luevitoonvechkij,S. (BMJ Publishing Group, 2015)
Dysplasia epiphysealis hemimelica or Trevor 's disease is a rare disorder of localised osteochondral overgrowth affecting the epiphysis of extremities. This paper reports a 12-year-old boy presenting with a large bony mass at the left ankle diagnosed as dysplasia epiphysealis hemimelica. The articular surface of the ankle joint of the patient was evaluated with preoperative and postoperative MRIs. The 2-year postoperative MRI showed early osteoarthritis of the ankle, therefore demonstrating the importance of early excision avoiding more complex resections of intra-articular lesions. Copyright 2012 BMJ Publishing Group. All rights reserved.